From pathogenesis to antigens: the key to shaping the future of TB vaccines - Yang, Haoyan; Lei, Xinkui; Chai, Siyu; Su, Guimin; Du, Lin (Frontiers in Immunology, 2024)
Tuberculosis (TB) remains one of the gravest global health challenges. Mycobacterium tuberculosis (M. tuberculosis), the causative agent, employs sophisticated immune evasion and pathogenesis strategies. Its capability to thrive within immune cells and incite robust inflammatory responses prolongs infection and dissemination. Mycobacterial advanced adaptations facilitate navigation through the human immune system and present a variable antigenic profile throughout different infection stages. Investigating these strategies unfolds targeted approaches to effective vaccine development against TB. This review delves into the most advanced and exhaustive insights into the immune evasion tactics and pathogenic processes of M. tuberculosis across various infection stages. The knowledge distilled from this analysis holds the promise of guiding the creation of innovative TB vaccines and translating theoretical groundwork into practical immunological defenses.